Application Of Group Supportive Therapy On Family Self-Efficacy In Caring For Children With Special Needs Atslb Tunas Mulia Nganjuk - Lingga Kusuma Wardani; Putri Ayu Venty El Hanief; Fajar Rinawati (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
ABK require different treatment than children in general. This makes parents have to play a bigger role in providing care. Parental self-efficacy greatly influences parenting patterns in educating ABK. Parents with low self-efficacy tend to treat their children badly. In contrast, parents with high self-efficacy will show sensitivity, responsiveness and active coping. This research was conducted to determine the application of supportive group therapy to family self-efficacy in caring for children with special needs at SLB Tunas Mulia Nganjuk. This research method uses a quantitative approach with a pre-experimental one-group pretest-posttest design with a simple random sampling technique of 32 respondents. The research subjects were parents of students at SLB Tunas Mulia Nganjuk. The research instrument is a self-efficacy questionnaire. Data analysis was carried out using the Wilcoxon statistical test. The research results of 32 respondents before being given group supportive therapy treatment fell into the moderate category with 29 respondents (91%). The low category was 2 respondents (6%), and the high category was 1 respondent (3%). Self-efficacy increased to the high category after being given group supportive therapy treatment by 29 respondents (91%). The medium category was 3 respondents (9%). The Wilcoxon statistical test shows a result of 0.000. The value is 0.000 <0.05, then the hypothesis is accepted, which means that providing supportive group therapy has an influence in increasing family self-efficacy in caring for children with special needs at SLB Tunas Mulia Nganjuk.